Zero Waste. Some Remarks About Copper Alloy Bowls Recycling in the High and Late Middle Ages - Andrzej Janowski (Fasciculi Archaeologiae Historicae, 2019)
The article presents the results of interpretation of a parts of a copper alloy bowls from the 10th-13th centuries. The vessels might have been originally used for liturgical ceremonies. We know a lot of bowls fragments from Europe that have been reworked as linings, ferrules or rivets. In all these examples we are dealing with metal recycling.